Reducing Crime and Violence : Experimental Evidence on Adult Noncognitive Investments in Liberia - Blattman, Christopher; Jamison, Julian C.; Sheridan, Margaret (World Bank, Washington, DC, 2016)
The paper shows that self-control, time preferences, and values are malleable in adults, and that investments in these skills and preferences reduce crime and violence. The authors recruited criminally-engaged Liberian men and randomized half to eight weeks of group cognitive behavioral therapy, fostering self-regulation, patience, and noncriminal values. They also randomized $200 grants. Cash alone and therapy alone dramatically reduced crime and violence, but effects dissipated within a year. When cash followed therapy, however, crime and violence decreased by as much as 50 percent for at least a year. They hypothesize that cash reinforced therapy's lessons by prolonging practice and self-investment.